2009
DOI: 10.1016/j.genhosppsych.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Success of mental health referral among pregnant and postpartum women with psychiatric distress

Abstract: Objective-This study measured rates of and determined factors associated with mental health service use among a cohort of 465 pregnant and postpartum women receiving care at publicly funded obstetrical clinics.Methods-Women underwent a diagnostic evaluation, were provided with at least one mental health referral, and were encouraged to seek treatment; follow-up with provision of additional referrals occurred at 1, 3, and 6 months after the initial assessment. Logistic regression was used to estimate the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 32 publications
4
98
2
Order By: Relevance
“…One study found that only 38.5% of women referred for psychiatric assessment attended at least one session, and only 6% continued treatment [34]. The drop-out rate in this study was also high: 50% at the six-month follow-up and 54% at the 12-month follow-up.…”
Section: Discussionmentioning
confidence: 47%
“…One study found that only 38.5% of women referred for psychiatric assessment attended at least one session, and only 6% continued treatment [34]. The drop-out rate in this study was also high: 50% at the six-month follow-up and 54% at the 12-month follow-up.…”
Section: Discussionmentioning
confidence: 47%
“…Within the traditional model, physicians provide patients with referrals to outpatient mental health providers. However, there are many barriers and limitations to the traditional referral model, including stigma, delayed access to services, and the lack of follow-up by many patients [3,5,19,23,27]. Additionally, many women experiencing depression during and after pregnancy prefer to receive treatment in their obstetric clinic rather than in an outpatient therapy setting [5].…”
Section: Access and Barriers To Carementioning
confidence: 99%
“…Despite the fact that several efficacious psychosocial treatments for depression exist [17], research has shown that the majority of pregnant and postpartum women, especially low income women, do not receive services because they do not follow up on referrals to outpatient mental health care [3, 23,24].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly the case when the women's health psychologist is integrated directly into the ob/gyn practice. Women's health patients are nearly four times more likely to follow up with behavioral health treatment when services are offered at the same site (Smith et al, 2009). …”
Section: Women's Health Patients Are Undertreated For Behavioral Healmentioning
confidence: 99%